2015
DOI: 10.5603/cj.a2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable everolimus-eluting vascular scaffold in patients with ST-segment elevation myocardial infarction: Optical coherence tomography evaluation and clinical outcomes

Abstract: Background: Bioresorbable vascular scaffold (BVS) implantation is a new, promising treatment method of coronary artery disease. Preliminary data in patients with (Cardiol J 2015; 22, 3: 315-322)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This registry suggested that when accurate BRS implantation technique was used, an unrestricted BRS use would be safe and effective. 17) 18) 19) 20) 21) In addition, BRS was evaluated in the complex patients and lesions subset including diabetes, 22) ACS, 23) 24) 25) MI, 26) 27) 28) 29) 30) 31) 32) 33) small vessel, 34) and in-stent restenosis. 35) 36) 37) However, the interpretation of such studies should be careful considering the biased nature of registry studies.…”
Section: Current Evidencementioning
confidence: 99%
“…This registry suggested that when accurate BRS implantation technique was used, an unrestricted BRS use would be safe and effective. 17) 18) 19) 20) 21) In addition, BRS was evaluated in the complex patients and lesions subset including diabetes, 22) ACS, 23) 24) 25) MI, 26) 27) 28) 29) 30) 31) 32) 33) small vessel, 34) and in-stent restenosis. 35) 36) 37) However, the interpretation of such studies should be careful considering the biased nature of registry studies.…”
Section: Current Evidencementioning
confidence: 99%
“…Of note, in the multivariate analysis, BVS was not associated with the incidence of MACE (P>0.9). More recently, Kochman et al 42 performed an OCT assessment of acute procedural results of BVS implantation in 23 STEMI patients, also evaluating midterm clinical outcomes. Procedural and clinical success rates were 95.7%, whereas the device success rate was 100%.…”
Section: Evidence For Bvs Use In Patients With Acute Coronary Syndromesmentioning
confidence: 99%
“…At the 30-day follow-up, the target lesion failure rate was 0% and no cases of cardiac death or ScT were observed. Kochman et al (23) performed an OCT assessment of acute procedural results of BVS implantation in 23 STEMI patients, demonstrating a high strut apposition rate (>95%) immediately after implantation. In a median follow-up period of 229 (range, 199-248) days, 1 MI, caused by sub-acute ScT, occurred in a patient who discontinued dual antiplatelet therapy (DAPT).…”
Section: Single-center Registriesmentioning
confidence: 99%